Fullfoder och blandfoder till mjölkkor - Isacson, Kajsa (2006)
Total mixed rations (TMR) and TMR complemented with individual grain feeding to dairy cows are a growing practice in Sweden. This is because the heard sizes of the farms are increasing. Some farmers and farm advisors in Sweden have great knowledge and practical experience of working with TMR. In the same time there are many advisors that do not know how to handle TMR and farms that have a group based feeding of their animals.